Naringenin-induced Oral Cancer Cell Apoptosis Via ROS-mediated Bid and Bcl-xl Signaling Pathway - Du, YuYe; Lai, Jia; Su, Jingyao; Li, Jiali; Li, Chuqing; Zhu, Bing; Li, Yinghua (Current Cancer Drug Targets, 2024)
Background: Oral cancer is a malignant tumor with a high impact and poor prognosis. Naringenin, a flavonoid found in citrus fruits and its anti-inflammatory and antioxidant properties offer potential therapeutic benefits. However, limited studies have been conducted on the impact of naringenin on human tongue carcinoma CAL-27 cells. This study aims to elucidate the correlation between naringenin and tongue cancer, thereby identifying a potential therapeutic candidate for drug intervention against tongue cancer. Methods: The effect of naringenin on the apoptosis of CAL-27 cells and its mechanism were studied by cell counting kit-8, mitochondrial membrane potential assay with JC-1, Annexin V– FITC apoptosis detection, cell cycle, and apoptosis analysis, Reactive Oxygen Species assay and Western blot. Results: The results showed that naringenin significantly induced apoptosis in CAL-27 cells in a dose-dependent manner. Mechanistically, naringenin-induced apoptosis was mediated through the upregulation of Bid and downregulation of Bcl-xl, which led to increased generation of ROS. Conclusion: The findings suggested that naringenin may represent a promising candidate for the treatment of oral cancer by inducing apoptotic cell death via modulation of the Bid and Bcl-xl signaling pathways.
Keywords: oral cancer